THE IMPLEMENTATION OF THE MANAGEMENT CONTROL SYSTEM IN THE ACCOUNTING SCHOLAR OF FACULTY ECONOMY AND BUSINESS AT CHRISTIAN UNIVERSITY OF INDONESIA WITH THE FOUR LEVERS OF CONTROL MODEL - Sianturi1), Santamay Soniwaty; Sidharta2), Juaniva (Fundamental Management Journal, 2020)
This study aims to find out how to implement management control systems in accounting scholar study programs with the four levers of control model. The level of this research is quantitative research. The data obtained in this study are primary data, namely the results of questionnaires and secondary data obtained from theses, e-journals. The population in this study are active students of accounting scholar program at FEB UKI in semester of 2017/2018 academic year. The sampling technique in this study is to use simple random sampling method. Data collection method in this study is using a questionnaire with a Likert scale. Keywords : Implementation of the Management Control System, The Four Levers of Control.